ANTI-CRISIS FACTORS OF COMPETITIVENESS OF SERVICE SECTOR ENTERPRISES - I. A. Troyan (Вестник университета)
The transformation of the socio-economic conditions of the functioning of service enterprises caused by the spread of the COVID-19 pandemic and the resulting economic crisis, actualize the study of the possibilities of ensuring their competitiveness. The article gives the analysis of the genesis and development of the content of the category of enterprise competitiveness in the basic concepts of economic theory. The author proposes a definition of the competitiveness of a service enterprise. The paper analyses traditional basic factors of enterprise competitiveness as well as substantiates the anti-crisis factors of maintaining the competitive maintenance of a service sector enterprise in the context of the current economic crisis related to the COVID-19 pandemic, such as: digitalization of business and the process of providing services, customer focus, virtualization of the workforce, cybersecurity, and the use of opportunities of the state anti-crisis policy.